NUTRITIONAL STATUS OF SCHOOL-AGE CHILDREN IN THE NKWANTA SOUTH DISTRICT - VOLTA REGION OF GHANA - Prince, Appiah Kubi; Laar, Amos (European Scientific Journal, ESJ, 2014)
Background: Childhood malnutrition is still a public health concern affecting both children and adolescents in Ghana. However, school-age children are not always included in national surveys. This study explored the prevalence of malnutrition among school-age children in the Nkwanta South District, of the Volta Region, Ghana. Methods: The study was cross-sectional in design involving school-age children aged 10-19 years in public basic schools in the district. A multistage sampling technique was used to select 650 respondents from schools on feeding programme and schools not on feeding programme. An anthropometric measurement of weight and height was measured by standard methods. Prevalence of overweight, thinness, and stunting was determined by WHO Z-scores criteria and cut offs points for school-age children.EpiInfo version 7 and Stata version 11 were used to enter and analyze data. Results: Three hundred and forty-seven (53.4%) of the sampled students/respondents were females. Respondents had a mean age of 13.4 years. Prevalence of overweight was 6.9%, stunting 50.3% and thinness 19.4%. Prevalence of stunting and thinness was higher among children in schools on feeding programme, while overweight was higher among children in schools not on feeding programme. Area of residence, community type, taboos/beliefs, sex, age, type of school, feeding programme, and some subdistricts were found to be associated with overweight, stunting and thinness. Conclusions: malnutrition rates in this study are higher than national averages for children under five years of age. Interventions such as public awareness and education on child and adolescent nutrition in the district, inclusion of adolescent nutrition in national surveys are recommended.